The Mediating Role of Individual Performance in the Interplay between ICTE Appropriation and Educational performance - Said Mdarbi; Lhoussain Simour; Chaimae Boufarouj; Zineb Belkebir; Khadija Stili; Mouad Ennadi (European Scientific Journal, ESJ, 2024)
Over the past two decades, higher educational institutions have invested heavily in information and communication technologies (ICT). Since the advent of the Internet, ICTs have significantly impacted university organization, teaching, and learning methods. A key research question concerns the impact of students' appropriation of ICTs on educational performance. Scholars have explored this question both theoretically and empirically but faced two main constraints. First, it is challenging to observe students' ICT appropriation due to unclear definitions. Second, the evolving nature of ICTs makes isolating their effects difficult. This study aims to explore the contribution of students' ICT appropriation to educational performance in universities and to define the role of Individual Performance in the relationship between ICT appropriation and educational outcomes. Based on a quantitative survey of students from public universities in the Casablanca-Settat region, the study used the structural equation method (SEM) with SMART PLS 4.0 software. Data from 185 students revealed a direct correlation between ICT adoption and educational performance, with individual performance acting as an intermediary. The findings indicate that ICT profoundly influences the learning process in higher education. Future research should focus on the individual performance of Moroccan university students and its impact on their educational outcomes.